Sugar (CTA WageningenNL, 2008)
Outlines the nature of the reform of the EU sugar regime, focusing on its principal impact - a reduction in prices - that will affect not only ACP producers but also EU beet farmers and sugar millers, for whom restructuring support is available. Considers how ACP countries could meet the challenges posed in the developing situation through technological adaptation, cost reduction and targeting investment into new markets, such as the 'luxury purchase' and 'fair trade' markets.
Keywords: SUGAR